2016
DOI: 10.1016/j.vaccine.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein complex vaccines induce antibodies against Neisseria meningitidis via a MyD88-independent mechanism

Abstract: N. lactamica and N. meningitidis HSPC vaccines both have potential utility for immunising against neisserial meningitis without the requirement for an exogenous adjuvant. The mode of action of these vaccines is highly complex, with HSPCs inducing immune responses via both MyD88-dependent and -independent mechanisms. In particular, these HSPC vaccines induced an antibody response without detectable T cell help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…6 As TLR2 and TLR4 are both dependent on MyD88 this is consistent with the original premise that HspC induce immunity via activation of cell surface TLR. However there remain several unanswered questions.…”
Section: Hspc Vaccine Induced Cellular Responsesupporting
confidence: 86%
See 4 more Smart Citations
“…6 As TLR2 and TLR4 are both dependent on MyD88 this is consistent with the original premise that HspC induce immunity via activation of cell surface TLR. However there remain several unanswered questions.…”
Section: Hspc Vaccine Induced Cellular Responsesupporting
confidence: 86%
“…In a study recently published in Vaccine we reported the first evaluation of the mechanism of action of an HspC vaccine. 6 This showed that, as predicted, the cellular response of mice to neisserial HspC vaccines was completely dependent on the TLR adaptor protein MyD88.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations